MENYOAL TANTANGAN BAWASLU DALAM MEWUJUDKAN INTEGRITAS PEMILU DAN PEMILIHAN 2024 - Rahmatunnisa, Mudiyati (Bawaslu Provinsi Jawa Barat, 2024)
This article analyzes the challenges faced by the Election Supervisory Body (Bawaslu) in ensuring electoral integrity during Indonesia's concurrent 2024 elections. Using qualitative methods and literature review, this study identifies various forms of electoral malpractice including institutional manipulation, voter preference manipulation, and vote count manipulation that threaten electoral integrity. The findings indicate that Bawaslu faces significant obstacles in performing its supervisory role effectively, including limited human resources, budget constraints, low public participation in election monitoring, and technological challenges. Additionally, the study reveals that criticisms of Bawaslu's performance center around slow response times to electoral violations and suboptimal law enforcement. This research contributes to understanding the complexities of electoral supervision and offers insights for improving future electoral processes in Indonesia.